Chronic Disease Self-Management Education (CDSME) Program Delivery and Attendance among Urban-Dwelling African Americans - Mingo, Chivon A.; Smith, Matthew Lee; Ahn, SangNam; Jiang, Luohua; Cho, Jinmyoung; Towne, Samuel D.; Ory, Marcia G. (Frontiers in Public Health, 2015)
Background Older African Americans carry a disproportionate share of chronic diseases. The purpose of this study was to identify the characteristics of urban-dwelling African Americans with chronic disease participating in Chronic Disease Self-Management Education (CDSME) programs and to examine factors related to successful program completion (i.e., attending at least four of the six sessions). Methods Data were analyzed from 11,895 African Americans who attended a CDSME program at one of the five leading delivery sites (i.e., senior center, health care organization, residential facility, community location, faith-based organization). Logistic regression analyses were used to assess the associations of demographic, delivery site, and neighborhood characteristics with CDSME program successful completion. Results Approximately, half of the African American participants were aged 65–79 years, 83% were female, and 92% lived alone. Approximately, 44% of participants had three or more chronic conditions and 35% resided in an impoverished area (i.e., 200% below federal poverty level). Successful completion of the CDSME program was associated with being between the ages of 50–64 and 65–79 years, being female, living alone, living in an impoverished community, and attending a CDSME program at a residential facility or community center. Conclusion Findings highlight the unique patterns of attendance and delivery within the context of self-management interventions among this unique and traditionally underserved target population. Understanding such patterns can inform policy and practice efforts to engage more organizations in urban areas to increase CDSME program adoption. Particularly, employing strategies to implement CDSME programs across all delivery site types may increase reach to African American participants.